(untitled) (Asian-Australasian Journal of Food Safety and Security, 2019)
The present study has been undertaken to assess the training needs of employer on cleaner production in SAF leather industry at Jashore district in Bangladesh. Using Borich Need Assessment Model for training needs. A total 60 employers were surveyed including 20 employers from each group and data were collected on socioeconomic condition of responders, management activities in leather processing and environment pollution related issues through the questionnaire. The importance level, competence needs were analyzed and ranked using weighted discrepancy scores (WDS). The study revealed that the highest WDS score (15.38) was found for Beam house worker that indicated the training is strongly needed for them on identification of harmful chemicals and environmental pollution. Crust and fishing unit worker needed high training (WDS score= 15.10) on understanding the types and quantities wastewater discharged from industry during leather processing and its management. The WDS score 14.78 was estimated for administrative employers where they needed high training on controlling odor problem from the industry. Although they have an average knowledge about the environmental pollution, they did not have qualified level of capabilities on understanding how to use some environmental tools e.g. social impact assessment and environmental auditing. Therefore, majority of the respondents preferred training for reduction of environmental pollution. Asian Australas. J. Food Saf. Secur. 2019, 3(1), 15-22